"The whole of humanity has lungs, doesn't it? We are not all the same sort of people": patient preferences and choices for an online, self-guided chronic breathlessness supportive intervention: SELF-BREATHE. Issue 3 (11th July 2022) - Reilly, Charles C.; Bristowe, Katherine; Roach, Anna; Chalder, Trudie; Maddocks, Matthew; Higginson, Irene J.
Introduction: The burden of chronic breathlessness on individuals, family, society and health systems is significant and set to increase exponentially with an ageing population with complex multimorbidity, yet there is a lack of services. This has been further amplified by the coronavirus disease 2019 pandemic. Online breathlessness interventions have been proposed to fill this gap, but need development and evaluation based on patient preferences and choices. This study aimed to explore the preferences and choices of patients regarding the content of an online self-guided chronic breathlessness supportive intervention (SELF-BREATHE). Methods: Semi-structured telephone interviews were conducted with adults living with advanced malignant and nonmalignant disease and chronic breathlessness (July to November 2020). Interviews were analysed using conventional and summative content analysis. Results: 25 patients with advanced disease and chronic breathlessness (COPD n=13, lung cancer n=8, interstitial lung disease n=3, bronchiectasis n=1; 17 male; median (range) age 70 (47–86) years; median (range) Medical Research Council dyspnoea score 3 (2−5)) were interviewed. Individuals highlighted strong preferences for focused education, methods to increase self-motivation and engagement, interventions targeting breathing and physical function, software capability to personalise the content of SELF-BREATHE to make it more meaningful to the user, and aesthetically designed content using various communication methods including written, video and audio content. Furthermore, they identified the need to address motivation as a key potential determinant of the success of SELF-BREATHE. Conclusion: Our findings provide an essential foundation for future digital intervention development (SELF-BREATHE) and scaled research. Patient preferences and choices will directly inform the content development of an online, self-guided chronic breathlessness supportive intervention (SELF-BREATHE) to optimise acceptability and potential for benefit https://bit.ly/3OX9PML